PLINs-mediated organelle interactions: a key of exercise-mediated improvement of skeletal muscle lipid metabolism disorders - Liu, Zhiyuan; Zhao, Yungang (Frontiers in Endocrinology, 2025)
Perilipins are essential structural proteins localized on the surface of lipid droplets, with perilipin 2, 3, and 5 exhibiting specific expression in skeletal muscle. Intramuscular lipids are predominantly stored within lipid droplets, tightly regulated by perilipins. Perilipin 3 primarily governs lipid droplet biogenesis, whereas Perilipin 2 and PLIN5 play critical roles in mediating lipolysis through lipid droplet-organelle interactions and in responding to exercise-induced signaling cascades. Acute exercise selectively depletes lipid droplets coated with Perilipin 2 and Perilipin 5 while inducing subcellular relocalization of perilipin proteins. In contrast, moderate-intensity continuous training and high-intensity interval training elicit adaptive alterations in skeletal muscle perilipins protein expression: Moderate-intensity continuous training significantly upregulates perilipin 2 and 5 expression, whereas high-intensity interval training specifically enhances perilipin5 expression, fostering enhanced physical interactions between lipid droplets and mitochondria, thereby mitigating ectopic lipid accumulation. This study elucidates the intricate regulatory mechanisms of perilipin-mediated organelle interactions under diverse exercise modalities and their contributions to optimizing skeletal muscle lipid metabolism, providing a robust theoretical framework for developing targeted exercise-based interventions and potential therapeutic targets for metabolic disorders.